2015
DOI: 10.14797/mdcj-11-3-160
|View full text |Cite
|
Sign up to set email alerts
|

AIBP: A Novel Molecule at the Interface of Cholesterol Transport, Angiogenesis, and Atherosclerosis

Abstract: Cardiovascular disease, which is often driven by hypercholesterolemia and subsequent coronary atherosclerosis, is the numberone cause of morbidity and mortality in the United States. Based on long-term epidemiological studies, high-density lipoprotein cholesterol (HDL-C) levels are inversely correlated with risk for coronary artery disease (CAD). HDL-mediated reverse cholesterol transport (RCT) is responsible for cholesterol removal from the peripheral tissues and return to the liver for final elimination. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…The NAD(P)HX dehydratase and epimerase are two members of a growing list of enzymes that have been recognized in recent years to participate in a process called metabolite repair or metabolite proofreading and in which a panoply of protective enzymatic activities are required to prevent the accumulation of non-canonical, potentially toxic metabolites that are formed continuously via enzymatic side reactions or spontaneous chemical reactions [11][12][13][14]. The NAXE protein has been reported by other investigators to play a role in cholesterol efflux and angiogenesis [15][16][17]; it remains unclear how this role could be reconciled with the metabolite repair function [18].…”
Section: Introductionmentioning
confidence: 99%
“…The NAD(P)HX dehydratase and epimerase are two members of a growing list of enzymes that have been recognized in recent years to participate in a process called metabolite repair or metabolite proofreading and in which a panoply of protective enzymatic activities are required to prevent the accumulation of non-canonical, potentially toxic metabolites that are formed continuously via enzymatic side reactions or spontaneous chemical reactions [11][12][13][14]. The NAXE protein has been reported by other investigators to play a role in cholesterol efflux and angiogenesis [15][16][17]; it remains unclear how this role could be reconciled with the metabolite repair function [18].…”
Section: Introductionmentioning
confidence: 99%
“…ApoAI binding protein (AIBP) is secreted from tissue and physically binds with apoAI (13). AIBP accelerates cholesterol efflux from endothelial cells to HDL-C thereby regulating angiogenesis via alterations in the composition of the lipid rafts, possibly due to reduced caveolin-1 (CAV-1) and as well as interfering with VEGFR2 signalling (14,15). Alteration in angiogenic factors have been repeatedly observed in pre-eclamptic placentae (16) with decreased VEGF-A and VEGFR1 in the cytotrophoblast.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that both AIBP and HDL-C mediated cholesterol efflux alters the composition of the lipid rafts, due to reduced CAV-1, as well as interfering with vascular endothelial growth factor receptor 1 (VEGFR2; KDR) dimerization and signalling, thus inhibiting VEGF-induced angiogenesis (14,15). The authors concluded that AIBP positively regulates cholesterol efflux from endothelial cells and that effective cholesterol efflux is critical for proper angiogenesis (14).…”
mentioning
confidence: 99%
“…In addition to the high-throughput screening identification of transthyretin (TTR) as a potential C . burnetii target involved in cholesterol processing [ 101 ], complementary testing confirmed two additional host proteins involved in cholesterol handling: the apolipoprotein APOA1BP [ 102 ] and the intracellular cholesterol transporter NPC2 [ 103 ]. Although C .…”
Section: Resultsmentioning
confidence: 99%